What factors are associated with the provision of assistive technologies: The Bogotá D.C. case (2014)
Aim: To examine what demographics and clinical factors are associated with the provision of assistive technology (AT) devices in a low-income country. Method: Retrospective cross-sectional exploratory study design including 15 of the 20 localities across Bogotá D.C., Colombia, a city with 6776009 inhabitants. Results: The type of AT device provided was significantly dependent (p less than 0.001) on the client's diagnosis, impairment, age, and socio-economic strata, whether the client has a care giver, the geographical zone in which the client lives, the year of the AT provision, and the total number of AT delivered. In contrast, the client's gender (p>0.05) and the client's affiliated type of healthcare service had no effect. In addition to that, the client's age, the client's socio-economic strata, the number of AT devices provided to the client, and the diagnostic type were the factors with the strongest level of association with the type of AT device provided. Conclusions: Our research showed that the provision of AT in Bogotá D.C. prioritizes both people who are at the highest levels of vulnerability, and as many people as possible with the budget. That is, the low socio-economic strata, younger and older people, and the provision of at least one AT device.Implications for RehabilitationProvision of AT is intended for equal opportunities for the social participation of people with a disability. Also, people with disabilities have the right to access AT regardless of the type of limitation, gender, race, age or region where they live.Research regarding AT in developing countries is scarce; thus, there is a need to conduct studies in such contexts. This study provides scientific evidence to support the development of models, approaches and strategies of AT provision in low-income countries where resources for rehabilitation are scarce. © 2014 Informa UK Ltd. All rights reserved.